Soybean pod and grain isoflavones accumulation during the filling period in field conditions - Carrera, Constanza Soledad (2021)
The objective of this work was to determine the isoflavones accumulation in soybean pods and grains during the filling period in field conditions. Pods of the same phenological stage (marked in R5, i.e. beginning of grain filling period) were collected at R5, R6 (full grain), and R7 (beginning of physiological maturity) stages. At each analyzed stage, grains always exceed pods isoflavone concentrations. A decreasing tendency of isoflavone concentration was observed in pods towards the late grain filling. In this maternal tissue, no acetyl glucosides at any stage or aglycones at physiological maturity were detected. In grains, glucosides, malonyl glucosides, and total isoflavones increased and acetyl glucosides decreased from R5 to R7, whereas aglycones increased to R6, but then decreased. It is concluded that grains are the main accumulation tissue of these bioactive compounds, whereas pods seem to contribute to their accumulation in advanced stages of grain development.